MENGUNGKAP KISAH DIBALIK NAMA “DESA KOTA LAMA” : WARISAN SEJARAH KERAJAAN INDRAGIRI - Yuliantoro Yuliantoro; Athira Agustin; Delka Yuni Zahra; Dian Andriani; Hendriadi Saputra; Mutia Hafizah; Roza Puspita Sari; Vinni Septri Wahdini; Viora Salsa Puja (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Many places have their own stories that can often provide lessons. However, many people do not know the origins of the area where they live, which triggers a sense of indifference to local identity and history in the local environment, as well as the case that the author found in Kota Lama Village. This research is expected to provide knowledge to the wider community about the identity and history behind the name Kota Lama Village. In compiling this research, researchers used a qualitative method with a descriptive approach and used a historical approach as a tool to examine and critically analyze the past phenomena under study. The results of the research indicate that the origin of the name of Kota Lama Village, which was once called the Kingdom of Negeri Menduyan, is inseparable from the historical story that occurred during the Indragiri Kingdom.